Inggris Inggris - Pradani, Fauziyyah Noumi Restu; Mustofa, Romy Faisal; Diella, Dea (Universitas Negeri Jakarta, 2024)
The purpose of this study is to determine the influence of differentiated learning on communication and collaboration skills of tenth-grade high school students at a school in Central Java on the topic of environmental change. The research method used was a Quasi Experiment with a posttest only-matching-only control group design. The population in this study is all high school class X students with a total of 288 students divided into 8 classes. In this study using the Non-probability Sampling technique in the form of purposive sampling. The samples in this study were class X E as the experimental class, totaling 36 students and class X G as the control class, totaling 36 students. The data collection technique was in the form of a non-test using a Collaboration Self-Assessment Tool (CSAT) questionnaire with 44 statement items and an oral communication skill observation sheet with 5 indicators as an aspect of observation. The data analysis technique used is the One Way Anova Test. Based on the results of the study, it was concluded that the use of differentiation learning strategies can improve students' communication and collaboration skills on environmental change materials.